The Influence of Financial Self-Efficacy, Risk Perception, Financial Literacy, and Herding on Investment Decision - Daffa Rizky Ramadhianto; Hartanti, Rina; Vivi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study examines the influence of financial self-efficacy, risk perception, financial literacy, and herding on investment decisions among Generation Z and Millennials in the Jabodetabek area. Motivated by the increasing participation of young investors in the capital market, the research highlights the psychological and behavioral factors influencing investment decisions. Using a quantitative approach, data were collected from 214 respondents via an online questionnaire. Structural Equation Modeling with Partial Least Squares (SmartPLS 4.0) was used for analysis. The results show that financial self-efficacy, risk perception, and financial literacy positively and significantly influence investment decisions at the 5% level, while herding has a positive and significant effect at the 10% level. These findings suggest that financial confidence, risk awareness, financial knowledge, and social influence are key drivers of investment behavior among young people. The study offers insights for investors, financial institutions, and policymakers to enhance financial literacy and encourage responsible investment practices.